Autoimmune hemolytic anemia after nivolumab treatment in Hodgkin lymphoma responsive to immunosuppressive treatment. A case report. Issue 4 (19th August 2016) - Tardy, Magalie P.; Gastaud, Lauris; Boscagli, Annick; Peyrade, Frederic; Gallamini, Andrea; Thyss, Antoine
Abstract : Abstract: The patients with refractory Hodgkin lymphoma have a poor prognosis. The nivolumab, an IgG4 monoclonal antibody inhibiting the program death 1 pathway has recently demonstrated its efficacy and its safety in patients with heavily pretreated refractory Hodgkin lymphoma. The side effects of this immunotherapy include autoimmune‐like syndromes. A 75‐year‐old woman with no significant comorbidities was treated by nivolumab (3 mg/kg every 2 wk) as a third‐line treatment for refractory Hodgkin lymphoma. A clinical response was observed with the first injection of nivolumab, with a reduction in superficial lymph nodes. After the second injection, the patient presented an authentic autoimmune hemolytic anemia with a profound anemia at 64 g/L and biologic characteristics of hemolysis (elevated unconjugated bilirubin, lactate dehydrogenase, and reticulocytes). The direct antiglobulin test was strongly positive for IgG antibodies, and the indirect antiglobulin test became positive with a very high level of autoantibodies. After 2 injections of nivolumab, the patient underwent a fluodeoxyglucose F 18 positron emission tomography‐computed tomography, showing a partial response according to modified Cheson criteria. A treatment with prednisone (2 mg/kg), initiated after transfusion of 2 units of red blood cells, permitted the complete resolution of this autoimmune reaction after 3 months of corticotherapy. The fluodeoxyglucose F 18 positron emission tomography‐computed tomography performed at the end of the corticotherapy showed a clear disease progression. Considering the very good response achieved after only 2 injections of nivolumab, the limited therapeutic resources for this old woman, and the complete resolution of the autoimmune hemolytic anemia, nivolumab was reintroduced at the same dose, with close clinical and biological monitoring. She received 6 more injections of nivolumab without recurrence of hemolysis.